Interactions between the intestinal microbiome and host genes in regulating vibriosis resistance in Cynoglossus semilaevis - Zheng, Weiwei; Chen, Yadong; Yang, Tao; Liu, Zhihong; Xu, Dong; Han, Huizong; Wang, Yaning; Xi, Xiaoqing; Wang, Tengteng; Chen, Songlin (Frontiers in Immunology, 2025)
BackgroundChinese tongue sole (Cynoglossus semilaevis) is now a commercially important flatfish species widely farmed in China. In recent years, frequent outbreak of vibriosis has caused high mortality rates and enormous economic losses to the aquaculture industry of Chinese tongue sole. The intestinal microbiome plays a crucial role in host immunity and protection against pathogen invasion. However, the interactions between the intestinal microbiome and host genes in vibriosis remain poorly understood.MethodsIn this study, we investigated the changes in intestinal histopathology, intestinal microbiome and host gene expression in resistant and susceptible individuals at 7 days post infection with Vibrio harveyi, and identified the host gene-microbe correlations. Histopathological sections were conducted to detected the histopathological changes in the posterior intestinal tissues of resistant and susceptible individuals. 16S rRNA sequencing was performed to characterize the changes in intestinal microbial community. RNA-seq was used for the identification of host differentially expressed genes (DEGs). The associations between intestinal microbes and host genes were illustrated by perform an integrated analysis of the differential intestinal microbes and host DEGs.ResultsObvious histopathological differences were observed between the resistant and susceptible groups in terms of inflammatory cells infiltration, and tissue dissociation of mucosal layer. 16S rRNA sequencing analysis indicated that Vibrio increased but Stenotrophomonas, Chryseobacterium, Delftia, and Salinivibrio decreased in the susceptible group. Compared to the control group, 1,986 differentially expressed genes (DEGs) were detected in the susceptible group, significantly more than the 310 DEGs found in the resistant group. DEGs in the susceptible group were significantly enriched in immune-related GO terms, such as antigen processing and presentation, MHC protein complex, and immune response, and pathways, including antigen processing and presentation, phagosome, and proteasome. Through an integrative analysis of differential intestinal microbes and host DEGs, 207 strong gene-microbe correlations were identified.ConclusionsThe results of this study indicate that V. harveyi infection severely damages the intestinal tissue and substantially alters the composition of intestinal microbiome and the expression of host genes, especially in susceptible individuals. Strong gene-microbe correlations may imply that the intestinal microbiome may interact with host genes to collectively regulate the vibriosis resistance in Chinese tongue sole, but the causality between them remains unestablished and requires further validation.